The History of a Genuine Fake Philosophical Treatise (Ḥatatā Zar’a Yā‘eqob and Ḥatatā Walda Ḥeywat). Episode 1: The Time of Discovery. From Being Part of a Collection to Becoming a Scholarly Publication (1852-1904) - Anaïs Wion (Institut des Mondes Africains, 2021)
In the middle of the nineteenth century, in the Ethiopian highlands, a Catholic missionary named Giusto d’Urbino chose to put an end to his evangelizing activities and resolved to devote himself fully to studying Ge’ez, Amharic, and Ethiopia’s Orthodox civilization. His mentor, Antoine d’Abbadie, was well-known at the time for his scholarly writings on Ethiopia. D’Urbino sent him the results of his work, in particular two copies of a very rare philosophical text, allegedly authored by an Ethiopian thinker in the seventeenth century. The present article is the first in a series devoted to the history and status of the Ḥatatā Zar’a Yā‘eqob and its appendix, the Ḥatatā Walda Ḥeywat. In order to show how these texts fit into Giusto d’Urbino’s oeuvre, this article draws on the manuscripts he sent to Antoine d’Abbadie, and analyzes the hitherto unpublished correspondence between the two men. As a linguist and translator, Giusto d’Urbino wanted to make a contribution to Ethiopian studies. His letters also suggest that he was an anxious and ambitious thinker, intent on producing a philosophical work. Might the two Ḥatatā have been a response to this twofold ambition?